The Revelation of the Potential Culture and Entrepreneurship: An Effort to Minimize the Unemployed Graduates of Salaf Islamic Boarding Schools in Tapal Kuda Areas, East Java, Indonesia - Haryono, Akhmad; Ariefianto, Lutfi; Supardi, Supardi; Suryaningtiyas, Ika Barokah; Hani, Evita Soliha; Iqbal, Muhammad (KARSA Journal of Social and Islamic Culture, 2019)
Islamic boarding schools are an alternative educational institution for people in East Java Tapal Kuda areas. Therefore, Islamic boarding schools have a very large contribution in the development of human resources. ThisÂ study aims at finding out the potential culture and entrepreneurship and the factors that can affect the unemployed graduates of the Salaf Islamic Boarding School. The qualitative approach method is used to achieve the research objectives. The data were obtained through participant observation and interviews with recording techniques and notes. As supporting data, quantitative data were also explored through questionnaires. The data obtained through interviews were then interpreted qualitatively, while quantitative data were in percentage in the form of tables and the results were then described. This study result found out that entrepreneurial behavior of graduates of the Salaf Islamic Boarding Schools can be categorized as very low. Some factors causing the high-unemployed graduates of Salaf Islamic Boarding Schools are factor of culture focusing only on religious books, factor of studentâ€™s very low education, factor of Islamic boarding schools curriculum that is not oriented on entrepreneurship, factor of parents’ low education, and factor of parentâ€™s economy. Among these factors, Salaf Islamic Boarding School curriculum factor is the most dominant because of no curriculum that can provide entrepreneurial skills to students (santri). Through changes in entrepreneurial oriented curriculum it is expected to reduce the unemployed graduates of Islamic boarding schools.